2005
DOI: 10.1001/archopht.123.12.1651
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Macula With Optical Coherence Tomography After Successful Surgery for Proliferative Vitreoretinopathy

Abstract: Objective: To use optical coherence tomography to assess the in vivo pathologic findings associated with incomplete visual recovery in patients who have undergone anatomically successful surgery to treat proliferative vitreoretinopathy. Methods: Eligible patients were recruited in vitreoretinal outpatient clinics between April 1, 2002, and July 31, 2003. Patients were included who had undergone anatomically successful vitreoretinal surgery to treat proliferative vitreoretinopathy and, at least 3 months after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Previously published studies found variable incidence rates of macular edema after surgery with silicone tamponade (18%–66%). 9,10 As reported by Dormegny et al 7 we found a negative correlation between BCVA and cysts area. However, we did not find any more difference in BCVA between MC− eyes and MC+ eyes, perhaps because of an insufficient statistical power resulting from the small size of our cohort.…”
Section: Discussionsupporting
confidence: 83%
“…Previously published studies found variable incidence rates of macular edema after surgery with silicone tamponade (18%–66%). 9,10 As reported by Dormegny et al 7 we found a negative correlation between BCVA and cysts area. However, we did not find any more difference in BCVA between MC− eyes and MC+ eyes, perhaps because of an insufficient statistical power resulting from the small size of our cohort.…”
Section: Discussionsupporting
confidence: 83%
“…The remaining eyes were diagnosed with exudative maculopathy (51.5%), macular atrophy (22%), and tractional maculopathy (21.5%), differently from previous reports. 4,26,27…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies had small sample sizes. 4,26,27 High reattachment rates, defining the anatomic success, are in contrast to the functional outcome, which is linked to preoperative and postoperative macular status. In our series, we found postoperative normal macular profile on OCT in 3% of successful cases.…”
Section: Discussionmentioning
confidence: 99%
“…7,34 Our visual outcomes compare favorably to previous reports; however, a study investigating poor visual outcomes (<20/40) after successful RD repair for PVR in 35 patients reported a 66% incidence of CMO. 41 Given the lower incidence of macular edema observed in the adjunct group, one might have expected a correspondingly better visual outcome, especially when excluding eyes with limited visual potential. This observation is potentially important suggesting that retinal pathology other than macular edema such as neural retinal remodeling 42 may be the primary cause of the poor visual outcomes seen in PVR.…”
Section: Discussionmentioning
confidence: 99%